1976
DOI: 10.1002/hlca.19760590229
|View full text |Cite
|
Sign up to set email alerts
|

Über die Konstitution von Loroglossin. Vorläufige Mitteilung

Abstract: The Constitution of Loroglossine. Loroglossine, a characteristic constituent of orchids, is shown to be bis‐[4‐(β‐D‐glucopyranosyloxy)‐benzyl]‐(2 R, 3 S)‐2‐isobutyl‐tartrate (1). Hydrolysis and esterification gave 1 mol‐equiv. of dimethyl (+)‐2‐isobutyl‐erythro‐tartrate ((+)‐3) and 2 mol.‐equiv. of a glucoside which, after acetylation, gave 4, identical with a synthetic sample. The erythro configuration of (+)‐3 by oxidation of isobutyl‐maleic acid with osmium tetroxide and subsequent esterification. The absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…(1975). In addition, Gray et al . (1976, 1977) showed that the configurations at C‐2 and C‐3 were ( R ) and ( S ), respectively.…”
Section: Structure and Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…(1975). In addition, Gray et al . (1976, 1977) showed that the configurations at C‐2 and C‐3 were ( R ) and ( S ), respectively.…”
Section: Structure and Physiologymentioning
confidence: 99%
“…The structure of loroglossin (shown in Pridgeon et al 2001) was determined to be bis[4-( β-glucopyranosyloxy)benzyl] erythroisobutyltartrate by Aasen et al (1975). In addition, Gray et al (1976Gray et al ( , 1977 showed that the configurations at C-2 and C-3 were (R) and (S), respectively.…”
Section: ⁽  ⁾   mentioning
confidence: 99%
“…6S (Supporting Information). According to the above information and after comparison with the previous literature [5][6][7][8][9][10][11], the two compounds were identified as bis [4-(β-D-O-glucopyranosyloxy)-benzyl] (S)-2-isopropylmalate (compound 1) and bis 4-[β-D-O-glucopyrnosyloxy)-benzyl]-(2R,3S)-2-isopropyl tartrate (compound 2), commonly known as vanilla glucoside A. (▶ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6S (Supporting Information). According to the above information and after comparison with the previous literature [5][6][7][8][9][10][11], the two compounds were identified as bis The potential biological activities of VPCE and compounds 1 and 2 were investigated through a series of biological activity experiments. Elastase is a serine protease that plays a crucial role in the wrinkling or sagging of the skin through the degradation of the elastic fibres of the dermis (elastin), causing the skin to lose its elasticity.…”
Section: Vanilla Pompona Leaves and Stems As New Sources Of Bioactive...mentioning
confidence: 99%
“…3 4 -O-Methylpiscidic acid dimethyl ester 2 has been isolated from Narcissus poeticus L. 1,2 and the glucoside loroglossin 4 is a characteristic constituent of orchids. 4 Structurally related eucomic acid 5 has been isolated from the bulbs of Eucomis punctata L'Hérit. Most of these structures can be seen basically as alkylated tartaric acid derivatives and although several syntheses of these compounds have been reported, 1,2,4 the work of Seebach 5 is notable for its concise approach.…”
mentioning
confidence: 99%